Replacement of barite by a (Ba, Ra)SO4 solid solution at close-to-equilibrium conditions: A combined experimental and theoretical study. (15th April 2015) - Brandt, F.; Curti, E.; Klinkenberg, M.; Rozov, K.; Bosbach, D.
Abstract: Solid solution formation between RaSO4 and BaSO4 has long been recognized as a process which potentially controls the Ra concentration in the environment. Here, we have systematically studied the replacement of pure barite by a (Ba, Ra)SO4 solid solution in 0.1 M NaCl through batch experiments extending up to 883 days at close-to-equilibrium (CTE) conditions, which are relevant to disposal of nuclear waste in a deep geological repository. Kinetic and thermodynamic models were applied to support the interpretation of the experiments, which were carried out at room temperature and at two distinct solid/liquid ratio (0.5 or 5 g/L). Different stages of recrystallization were observed, based on the rate of removal of Ra from aqueous solution. After a first slow kinetic step, a change in the slope of the aqueous Ra concentration vs. time is observed, suggesting nucleation of a new (Ba, Ra)SO4 phase from supersaturation. If this stage was considered to reflect equilibrium between aqueous and solid solution, one would infer ideality or even negative interaction parameters ( a 0 ⩽ 0). After this fast nucleation step, in the 0.5 g/L experiments the Ra concentrations in the aqueous solution slowly increase, approaching a concentration close to that required for equilibrium with a regular (Ba, Ra)SO4 solid solution with an interaction parameter a 0 = 1.0. Therefore, these data suggest a non-equilibrium Ra entrapment during the nucleation phase of the replacement, followed by slow recrystallization toward true thermodynamic solid solution equilibrium. Moreover, an interaction parameter value of a 0 = 1.0 was inferred from our experiments, which is in good agreement with theoretical predictions from atomistic simulations. A key result from this study is that aqueous solution and binary (Ba, Ra)SO4 approach full thermodynamic equilibrium within laboratory time scales (2.5 years). This justifies assuming complete thermodynamic equilibrium for this system in geochemical calculations of processes occurring on geological time scales. This finding is of direct relevance for the safety assessment of radioactive waste disposal, since it may constrain the solubility and thus the mobility of Ra in such environments.